Robust PID Auto-tuning for the Quadruple Tank System. Issue 7 (2016) - Ionescu, Clara M.; Maxim, Anca; Copot, Cosmin; De Keyser, Robin
Abstract: In multi-modular process architectures with independent but interacting subsystems, identification may not be the first choice at hand for closed loop control. A robust relay-based PID autotuning strategy is presented and validated on a quadruple tank system with non-minimum phase dynamics. The controller ensures a specified closed loop robustness, which is of great benefit to the overall performance. The experimental results suggest that the proposed method fulfils the robustness requirement and performs well in various operating conditions of the testbench.